Ultrasound Reversible Response Nanocarrier Based on Sodium Alginate Modified Mesoporous Silica Nanoparticles - Li, Xiaochong; Wang, Zhanhua; Xia, Hesheng (Frontiers in Chemistry, 2019)
Mesoporous silica nanoparticles (MSN) covered by polymer coatings cross-linked by weak coordination bonds were expected to present a reversible responsiveness under on-off ultrasound stimuli. Herein, we prepared a sodium alginate (SA) modified MSN with carboxyl-calcium (COO--Ca2+) coordination bonds in the modified layer, which could block the mesopores of MSN and effectively prevent the cargo pre-releasing before stimulation. The coordination bonds would be destroyed under the stimulation of low intensity ultrasound (20 kHz) or high intensity focused ultrasound (HIFU, 1.1 MHz), leading to a rapid and significant cargo release, and then they could be reformed when ultrasound was turned off, resulting in an instant cargo release stopping. The reversible cleavage and reformation of this coordination bonds under on-off ultrasound stimulus were confirmed by the gel-sol transition behaviors of the SA-CaCl2 gel. An excellent real-time control of rhodamine B (RhB) release performance was obtained under the ultrasound stimuli. Obviously, the cargo release ratio could reach to nearly 40% when HIFU (80 W) was turned on for 5 min, and remained basically constant when ultrasound was turned off, which would finally reach to nearly 100% within 30 min under this on-off pulsatile status. These hybrid MSN based nanoparticles with excellent reversible ultrasound on-off responsiveness were of great interest in on-demand drug delivery applications in the future.